THE RELATIONSHIP AMONG LEARNING MOTIVATION AND LEARNING FACILITIES WITH MATHEMATICS LEARNING OUTCOMES - Rahayu Ekowati; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Student learning motivation is still low, and learning facilities owned by students are still inadequate. This study aims to determine whether there is a positive and significant relationship between learning motivation and learning facilities with mathematics learning results in class X of State Vocational High School (SMK N) 5 Yogyakarta Semester Even 2017/2018 Academic Year. This type of research uses quantitative research. This study's population were students of class X SMK N 5 Yogyakarta Even Semester 2017/2018 Academic Year, consisting of 2 classes totaling 64 students. Class X Ceramic Craft B as the research sample class was taken by random sampling technique. Data collection techniques using the questionnaire method to obtain learning motivation data and learning facilities and test methods to obtain data on mathematics learning outcomes. Research instrument test: validity test, different power test, and reliability test. Analysis prerequisite tests include normality test, linearity test, and independence test. Data analysis using product moment analysis and multiple linear regression analysis. The results showed a positive and significant relationship between learning motivation and learning facilities with mathematics learning results in class X Ceramic Craft B of SMK N 5 Yogyakarta Even Semester 2017/2018 Academic Year. This is indicated by Fcount=  and Ftable =  so that Fcoun > Ftable, with the multiple correlation coefficient R2 =  and the multiple variable regression equation . Relative contribution  and  =  and effective contribution =  = .